Pengaruh Citra Produk, Harga Produk, Dan Pengurangan Harga Terhadap Keputusan Pembelian Kosmetik di Toko Vivi Kosmetik Kampung Pajak Kampung Pajak - Hutagaol, Anita (Universitas Labuhanbatu, 2024)
This study aims to analyze the effect of product image , Product Price and price reduction on cosmetic purchasing decisions at Kampung Pajak VIVI Cosmetics stores to determine the effect of product image, Product Price and price reduction on purchasing decisions with a sample of 96 people. Data collection techniques carried out by questionnaires or primary data. Data analysis techniques using descriptive statistics and multiple linear regression analysis. The results showed that simultaneously the influence of product image , Product Price, and product discount variables have a positive and significant effect on the purchase decision of cosmetics in the store VIVI Cosmetics with the value of F count 31.238 greater than Ftable 2.68 with a significant value of 0.000<0.05, partially the image of the product has a positive and significant effect on the purchase decision of cosmetics in the store VIVI cosmetics obtained a value of thitung3, 870 greater than ttable 1.66, Partially the price has a positive effect but not significant to the decision of the consuent to buy with t count 1.057 is smaller than ttable 1.66 and the probability value of t is 0.293 > 0.05, partially the price reduction has a positive effect and significant to the consuent decision to buy obtained the value of ttable 4.560 > ttable 1.66 and the probability value of t is 0.000 < 0.05.